The first nurse practitioner graduate programme in Japan. (29th August 2014) - Fukuda, H.; Miyauchi, S.; Tonai, M.; Ono, M.; Magilvy, J.K.; Murashima, S.
Abstract : Aim: This paper describes the establishment of the first Japanese nurse practitioner graduate programme and legislative activities to institutionalize nurse practitioners in Japan. Background: To address the super‐ageing population, Oita University of Nursing and Health Sciences initiated the first academic graduate level nurse practitioner programme in Japan, based upon the global standard defined by the International Council of Nurses. Conclusion: In 2010, Oita University of Nursing and Health Sciences graduated the first nurse practitioner. We believe that nurse practitioners will be highly valued in Japan for thoughtful nursing care to the fragile elders living in rural and urban Japan.